2015
DOI: 10.1111/ane.12542
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of stroke rehabilitation; data from two national cohorts

Abstract: Although components of the rehabilitation are reported as being the same, characteristics and the outcome of the inpatient rehabilitation are different. Therefore, comparison of stroke rehabilitation between countries requires caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[3][4][5] Recovery after stroke generally means improvements in physical, emotional, and cognitive function, as well as the capacity to perform daily activities. 5,[7][8][9][10] To reflect upon "person-centered practice," a person's experience of involvement must be central for participation. 5,[7][8][9][10] To reflect upon "person-centered practice," a person's experience of involvement must be central for participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Recovery after stroke generally means improvements in physical, emotional, and cognitive function, as well as the capacity to perform daily activities. 5,[7][8][9][10] To reflect upon "person-centered practice," a person's experience of involvement must be central for participation. 5,[7][8][9][10] To reflect upon "person-centered practice," a person's experience of involvement must be central for participation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Having a stroke has shown to have a negative impact on the level of perceived participation over time, even for persons with mild stroke. 5,[7][8][9][10] To reflect upon "person-centered practice," a person's experience of involvement must be central for participation. 11 In this article, the following definition of participation 11 is used; participation occurs at the intersection of what a person can do, wants to do, has the opportunity to do, and is not prevented from doing by the world in which the person lives and seeks to participate in.…”
mentioning
confidence: 99%
“…Comparisons of health services between countries can be challenging, and observed differences in patient outcomes and access may be heavily influenced by differences in financial models, availability of resources, and clinical guidelines or traditions [51, 52]. In this study, we have compared two countries with similar characteristics: high-income countries with universal health care where private health insurance is supplementary [25].…”
Section: Discussionmentioning
confidence: 99%
“…From other countries, it has also been shown that more effective strategies are needed to motivate patients to fulfill a complete follow-up and to obtain appropriate rehabilitation. 34,35 Furthermore, a system with education, support, and advice to patients and primary care has been found effective to control risk factors for recurrent stroke. 36…”
Section: Discussionmentioning
confidence: 99%